The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1161/01.cir.0000036014.90197.fa
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Remodeling After Primary Coronary Angioplasty

Abstract: Background-We prospectively evaluated the prevalence, pattern, and prognostic impact of left ventricular (LV) remodeling after acute myocardial infarction (AMI) successfully treated with primary PTCA. The prevalence, course, and prognostic value of LV remodeling after primary PTCA are still to be clarified. Methods and Results-In 284 consecutive patients with AMI treated with primary PTCA, serial echocardiographic and angiographic studies, within 24 hours (T1), at 1 (T2) and 6 months (T3) after AMI were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
186
3
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 519 publications
(211 citation statements)
references
References 30 publications
16
186
3
6
Order By: Relevance
“…We observed that infarct size and severity could be significant predictors of LV remodelling. Several clinical studies demonstrated that various parameters are predictive of remodelling, including anterior infarct location, patency of the infarctrelated artery, perfusion and functional parameters [4][5][6][7][8][9][10][11][12][13]. In agreement with these previous findings, the present study showed a number of baseline parameters predictive of remodelling, infarct severity demonstrating the best predictive value.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We observed that infarct size and severity could be significant predictors of LV remodelling. Several clinical studies demonstrated that various parameters are predictive of remodelling, including anterior infarct location, patency of the infarctrelated artery, perfusion and functional parameters [4][5][6][7][8][9][10][11][12][13]. In agreement with these previous findings, the present study showed a number of baseline parameters predictive of remodelling, infarct severity demonstrating the best predictive value.…”
Section: Discussionsupporting
confidence: 90%
“…In disagreement with these data, studies exploring functional abnormalities by echocardiography [9,10] or the presence of Q waves on the electrocardiogram [11] indicated that infarct transmurality and the presence of residual viability in the infarct territory could be more important than the infarct size in influencing LV remodelling. The relation between infarct severity and LV functional outcome was also confirmed in gated SPECT studies, showing that infarct severity was more effective than infarct size for predicting subsequent LV remodelling [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The moderate (MOD) remodeling phenotype was defined as a LVEDV and/or LVESV that was >20% higher than the average value in sham. We used the 20% cutoff change in volume as a marker of more significant remodeling as previously described 14, 15…”
Section: Methodsmentioning
confidence: 99%
“…11 According to the presence or absence of LV dilatation at 6 months after infarction, patients were divided into an LV remodeling group or a no LV remodeling group, respectively. Successful PTCA was defined as the restoration of TIMI 3 grade flow and residual stenosis Ͻ30% at the end of the procedure.…”
Section: Definitions and Outcome Measuresmentioning
confidence: 99%
“…11,12 Multiple factors may contribute to LV remodeling at different stages, from the time of coronary occlusion until the development of ventricular dilation and dysfunction. Infarct size, 13 anterior infarct location, 14 transmural extent of necrosis, 9 perfusional status of the IRA, 15 heart failure on admission, 16 and restrictive pattern of LV filling 17,18 have been identified as major predictors of LV dilatation after myocardial infarction in various patient populations.…”
Section: Microvascular Dysfunction and LV Remodelingmentioning
confidence: 99%